Development of the Environmental Visualization System Based on ESP32-CAM - Yevsieiev, V.; Luchaninova, O. (European Scientific Platform, 2022)
One of the promising areas of our time in the development of robotics is the development of humanoid robots. Research in this field makes it possible to synthesize various directions of modern technologies, such as computer vision systems, systems for identifying and recognizing objects based on neural networks, control, and decision-making systems under uncertainty.
Keywords: Robotics; Visualization System